PENGELOLAAN FASILITAS PENGUNJUNG EKOWISATA MANGROVE DI BANDAR BAKAU KOTA DUMAI - Alqarni, Wayis; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aimed about (1) Condition mangrove ecotourism visitor facilities at Bandar Bakau Dumai City. (2) the shape of the management of mangrove ecotourism visitor facilities in Bandar Bakau Dumai City.This study was a qualitative descriptive. This research subject is the key Informan namely, the Chief Manager of Bandar Bakau (PAB), Head of Tourism Department of Tourism Culture Youth and Sports Dumai, mangrove communities around the city, and in addition that Informen Visitors Bandar Bakau.The results showed that the condition of visitor facilities available in Ecotourism Mangrove, Mangrove Bandar Bakau Dumai City less good, because it is less manageable and lack of hygiene of the manager.Organizing shape (organaizing) lodging facilities, food and baverage and support industries not well organized yet appointed a separate manager for each of its facilities. Forms of Implementation (actuacting) lodging facilities, food and baverage and support industries less well, the implementation of these mangrove city manager should continue to control the existing facilities, so in case of direct damage repaired. Shape Control (controlling) facilities lodgings, food and baverage and support industries poor, lack of attention from the government in surveillance, lack of mobilization and supervision of the leader / boss of the existing facilities in the city of mangroves, and lack of organizational strong in developing facilities in Ecotourism Mangrove Mangrove Bandar Kota Dumai.Keywords : Management, Facilities, Ecotourism, Bandar Bakau.